Pengaruh Konsentrasi Etanol Pada Metode Ultrasonikasi Terhadap Aktivitas Antioksidan Ekstrak Daun Gonda (Sphenoclea zeylanica) - Intan Hartanti, Anisa; Mayun Permana, I Dewa Gede; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This study research aimed to determine the concentration of ethanol solvent affects the antioxidant activity of gonda leaf extract and determine the correct ethanol concentration to produce gonda leaf extract with the highest antioxidant activity using the ultrasonication method. This study used a Completely Randomized Design with ethanol concentration treatment consisting of five levels, namely 50%, 60%, 70%, 80%, and 90%. All treatments were repeated three times in order to obtain 15 experimental units. The parameters observed included yield, total phenol, total flavonoids, total tannins and antioxidant activity. The data obtained were analyzed by analysis of variance, if the treatment had a significant effect it would be followed by Duncan Multiple Range Test. The results showed that the ethanol concentration had a significant effect on yield, total phenol, total flavonoids, total tannins, and antioxidant activity. The results showed that 70% ethanol concentration was the best treatment with the highest antioxidant activity of 75.75 % with IC50 value of 123.38 mg/L, yield 22.86 %, total phenol extract GAE/g 40.94 mg, flavonoids. total 23.48 mg QE/g, total tannins 82.10 mg TAE/g.